CLASSIFICATION OF MARKETING MUTUAL FUNDS - O. Avelicheva (Вестник университета)
We consider a variety of UIF proposed a comprehensive classification of marketing UIF by various criteria, specific features of classification of various types of marketing. Proposed implementation of services of UIF and considered evaluation of economic efficiency and effectiveness of the image and the quality of services.